Factors impacting hunter access to private lands in southeast Minnesota. Issue 2 (4th March 2018) - Walberg, Eric; Cornicelli, Louis; Fulton, David C.
ABSTRACT: White-tailed deer (Odocoileus virginianus) have important socioeconomic and ecological impacts in the United States. Hunting is considered to be important for the effective management of deer and relies on access to privately owned lands. In 2013, we surveyed nonindustrial private landowners in southeast Minnesota and created two logit models to examine factors that impact landowners' decision to (a) allow public hunting access and (b) post private property. Parcel characteristics were found to impact landowner decisions to allow hunting access, particularly the size of the property and whether it was posted. Hunting access to small properties was more likely to be restricted to family, friends, and neighbors (83%) compared to medium (74%) or large properties (60%). Hunter concerns (e.g., liability) and knowledge about deer management was significant in both models, suggesting there are opportunities to educate landowners about the importance of allowing public hunting access and available liability protections.